PENGEMBANGAN MEDIA KARTU BERGAMBAR BERBASIS BUDAYA LOKAL PADA PEMBELAJARAN TEMATIK TEMA INDAHNYA KERAGAMAN DI NEGERIKU - Yuna Chairuna Pulungan,; Nurmairina, (Jurnal Cakrawala Ilmiah, 2024)
This research aims to develop picture card media based on local wisdom that is suitable for use in thematic learning on the theme "The Beauty of Diversity in My Country" in class IV elementary school. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages. The test subjects in this research were media experts, material experts, learning experts and student responses. The object of this research is picture card media based on local wisdom in thematic learning with the theme "The Beauty of Diversity in My Country" which is suitable for use in the learning process in class V. The instrument used to collect data is a validation questionnaire given to several expert validators, namely validators. media expert, material expert validator and learning expert validator. The total score obtained from validation by media experts was 97.6, from validation by material experts, namely 85.4, from learning experts it was 96.6 and from student responses a score was obtained of 94.2. The average score from the experts' assessments is 93.45. From this score, it can be said that the picture card media based on local wisdom that was developed is "very suitable" for use in the thematic learning process in class IV of SD Negeri 112137 Rantau Utara